The Use of Cake Application to Improve Speaking Skill at Ninth Grade of SMPN 11 Pekanbaru - Annisa Azzuhra; Zul Amri (Universitas Negeri Padang, 2023)
Speaking skill is not easy for many people, especially students. Some of the difficulties experienced by students are related to speaking skills which are included in the aspects of speaking English. Digital learning media is one kind of learning media that is often used today because it is easy to use and can increase student interest in learning. This research aims to analyze the speaking skill of junior high school students, especially at ninth grade of SMPN 11 Pekanbaru and to find out the effectiveness of Cake Application on the improvement students speaking skill. The focus on the study at ninth grade of junior high school because they still have difficulity in speaking even though they already get adequate English material that is learned from the seventh grade. The method of the study was using pre-experimental research with one-group pretest-posttest design. The findings of data analyzed showed that the mean score of speaking skill students (47.35) was included in the poor level category according to Harris (1996) while after giving the treatment ,the mean score posttest increases (69.35) which can be classified into the good level category. In conclusion, it means that the null hypothesis (H0) was rejected, while the alternative hypothesis (Ha) was accepted. Thus, Cake Application is effective to improve students’ speaking skill.